Structuring the Islamic Religious Education Learning Environment to Strengthen Students' Social Development - Mutmainah, Shania; Fakhruddin, Agus; Nugraha, Risris Hari (Al-Fikru: Jurnal Ilmiah, 2024)
A conducive learning environment is an important factor in creating learning experiences that support the formation of social values. With regard to that, SD negeri 132406 Tanjung Balai has implemented efforts to organize the learning environment for Islamic religious education in order to strengthen the social development of students. So this research will focus on analyzing these efforts, using qualitative methods based on case studies. The results show that structuring the Islamic Religious Education learning environment which includes social, personal, natural and cultural aspects effectively supports students' social and character development. Through an inclusive approach, social interaction, group work and the use of the natural environment, students can understand Islamic values and appreciate diversity. This arrangement strengthens social cohesion, communication skills and appreciation of differences and supports Islamic education's goal of forming students with good character who are ready to contribute to society. The implication of this research shows that structuring the learning environment that involves social, personal, natural and cultural aspects can be an effective model in shaping student character.